587 Utility of stabilometric footboard in prevention of work accident from fall. an italian study in a population of at-height workers. (24th April 2018) - D'Orso, Marco Italo; Riva, Michele Augusto; Invernizzi, Ilaria; Grosso, Daniele; Cesana, Giancarlo
Abstract : Introduction: Precipitations at workplaces still are a frequent cause of severe or mortal work accidents in Italy. Evaluation of at-height work suitability is by now carried out using many different medical clinical protocols usually based on clinical otorhinolaryngoiatric visit. This visit is frequently carried out with clinical tests the evaluation of which is merely subjective and therefore not always comparable. Methods: To verify the possibility of increasing accuracy of evaluation of at-height workers and to better point out workers hyper susceptible to fall, we experimentally insert in our usual clinical otorhinolaryngoiatric protocol an instrumental balance evaluation carried out using a stabylometric computerised footboard (ARGO Balance Static Force Platform RGMB) collecting contemporaneously 27 items. The clinical specialised otovestibular examination was composed by a specialised anamnesis, an otorhinolaryngoiatric medical examination, evaluation of tonic segmentary deviations, Romberg Test, research of spontaneous nystagmus, Barany test, Weits test. We compared the results of clinical and instrumental examination in 2.082 male workers aged from 18 to 65 years engaged in at-height work. Results: 1.775 of patients included in the research have been defined as suitable for at-height work after the otorhinolaryngoiatric clinical evaluation carried out in an Occupational Health Medical Surveillance. Among them 93 had pathological results at footboard. This fact originates after six months in these workers a second clinical and instrumental examination which in 12 cases has motivated a change in workers' specific work suitability. We report the different clinical and instrumental pathological patterns evidenced among the workers. Discussion: Stabylometric footboard seems to be a valid instrument to increase possibility of detection of at-height workers hyper susceptible to fall. Instrumental evaluation must be associate with medical clinical specialised examination. Our results have to be confirmed in larger studies having the aim of better define objective parameters of a normal balance in general population.